KORELASI SEBARAN GASTROPODA DAN BAHAN ORGANIK DASAR PADAEKOSISTEM MANGROVE DI PERAIRAN PANTAI PAYUM, MERAUKE - Sendy Lely Merly; Sisca Elviana (AGRICOLA, 2017)
Coastal area of Payum as an areaof mangrove forest located at western of Merauke Regency. Known as area which produce a high amount of organic matters, whether comes from mangrove area itself, stream or even by sea currents. They’re so much living organism associated with mangrove, one of them is gastropods. Sample was collected using transect quadran methods. The quadran size 5 x 5 m and the gastropods were collected as well as the sediment and sea water to measure the organic matter content. At that time the environments parameters also collected such as temperature, salinity and pH. The research result were successful identified 13 species of gastropods, like Cassidula angulifera, Littoraria scabra, Terebralia sulcata, Cerithidea obtusa, Neripteron violaceum, Indothais rufotincta, Nassasius unicolor, Tanea lineata, Nerita balteata, Turritella terebra, Glossaulax bicolor, Mitra sp. and Telescopium telescopium. Furthermore, the sediment analisys showed strong correlation      (60 % ) with the existence of gastropoda, reverse with sea water analisys which is had weak correlation around 10% of correlation value. Evenness index was high and followed by low of dominance index. Diversity index were high in stasiun I and II. Moreover, the density and frequency relative of gastropod spesies in every stasiun was dominate by Littoraria scabra.